Association between triage level and outcomes at Médecins Sans Frontières trauma hospital in Kunduz, Afghanistan, 2015. Issue 8 (10th November 2021) - Daebes, Hadjer Latif; Tounsi, Linnea Latifa; Nerlander, Maximilian; Gerdin Wärnberg, Martin; Jaweed, Momer; Mamozai, Bashir Ahmad; Nasim, Masood; Trelles, Miguel; von Schreeb, Johan
Abstract : Background: Five million people die annually due to injuries; an increasing part is due to armed conflict in low-income and middle-income countries, demanding resolute emergency trauma care. In Afghanistan, a low-income country that has experienced conflict for over 35 years, conflict related trauma is a significant public health problem. To address this, the non-governmental organisation Médecins Sans Frontières (MSF) set up a trauma centre in Kunduz (Kunduz Trauma Centre (KTC)). MSF's standardised emergency operating procedures include the South African Triage Scale (SATS). To date, there are few studies that assess how triage levels correspond with outcome in low-resource conflict settings Aim: This study aims to assess to what extent SATS triage levels correlated to outcomes in terms of hospital admission, intensive care unit (ICU) admission and mortality for patients treated at KTC. Method and materials: This retrospective study used routinely collected data from KTC registries. A total of 17 970 patients were included. The outcomes were hospital admission, ICU admission and mortality. The explanatory variable was triage level. Covariates including age, gender and delay to arrival were used. Logistic regression was used to study the correlation between triage level and outcomes. Results: Out of all patients seeking care, 28.7% were triaged as red or orange. The overall mortality was 0.6%. In total, 90% of those that died and 79% of ICU-admitted patients were triaged as red. Conclusion: The risk of positive and negative outcomes correlated with triage level. None of the patients triaged as green died or were admitted to the ICU whereas 90% of patients who died were triaged as red.